2005
DOI: 10.1158/1078-0432.ccr-04-2146
|View full text |Cite
|
Sign up to set email alerts
|

Defects in the Human Leukocyte Antigen Class I Antigen Processing Machinery in Head and Neck Squamous Cell Carcinoma: Association with Clinical Outcome

Abstract: Purpose: Human leukocyte antigen (HLA) class I antigen defects, which are frequently present in head and neck squamous cell carcinoma (HNSCC) cells may provide the tumor with an escape mechanism from immune surveillance. Scanty information is available about mechanisms underlying HLA class I antigen defects in both lesions and cell lines from HNSCC. In this study, we investigate the role of antigen processing machinery (APM) component abnormalities in the generation of deficient HLA class I surface expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
183
1
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 226 publications
(195 citation statements)
references
References 39 publications
7
183
1
4
Order By: Relevance
“…Similar to other HNSCC, having high expression of HLA class I was recently shown to correlate to better outcome in HPV − tonsillar and base of tongue SCC, while surprisingly having absent/weak expression correlated to a better prognosis in HPV + tonsillar and base of tongue SCC (20,(31)(32). Here, the corresponding correlations were not found.…”
Section: Discussionmentioning
confidence: 50%
“…Similar to other HNSCC, having high expression of HLA class I was recently shown to correlate to better outcome in HPV − tonsillar and base of tongue SCC, while surprisingly having absent/weak expression correlated to a better prognosis in HPV + tonsillar and base of tongue SCC (20,(31)(32). Here, the corresponding correlations were not found.…”
Section: Discussionmentioning
confidence: 50%
“…18 Using immunohistochemistry, Meissner et al have reported that HLA class I antigens were not detectable in 12% of the lesions from SCCHN. 19 It is generally accepted that IFN-γ transcriptionally modulates the expression of HLA class I antigens and of antigen processing machinery components, including the proteasome subunits LMP2, LMP7, and LMP10. 20 However, when Gun-1 cells were treated with IFN-γ and examined for HLA-A2 expression by flow cytometry, we failed to up-regulate HLA-A2 expression on these cells.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, down-regulation of MHC class I surface expression correlates in primary lesions with thickness, advanced disease stage, as well as with shorter time to progression rates. Correlations between MHC class I APM abnormalities and the clinical outcome of patients have not only been described for melanoma, but also for other malignancies including RCC, prostate, cervical, ovarian, and head and neck squamous cell carcinoma (Atkins et al, 2004;Ferris et al, 2006;Kageshita et al, 1999;Mehta et al, 2008;Meissner et al, 2005;Vitale et al, 1998). In prostate cancer, down-regulation of MHC class I molecules did correlate with higher progression rates and early tumor recurrence, which can be further accompanied with reduced or even loss of TAP1 and ERAP1 expression levels (Norell et al, 2006;Seliger et al, 2010).…”
Section: Alterations In Mhc Class I Antigen-processing Machinery Compmentioning
confidence: 98%